Computational Modelling and Design of Cathode Materials for Sustainable Energy Applications - Mates Torres, Eric (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2022)
Unravelling the activity and selectivity of novel heterogeneous catalysts requires a deep understanding of the effects unfolding at the catalytic surface. Particularly, this thesis emphasises the relevance of dopant distribution, ligand phase composition and surface coverage under electrochemical conditions for the theoretical study (supported by experiments) of photocatalytic and electrocatalytic systems for sustainable energy applications. To shed some light on the nature of these effects, three state-of-the-art electrocatalysts and their use for relevant reduction reactions were analysed computationally. Firstly, the role of N-dopants on the activity of metal-free C-based electrodes towards the oxygen reduction reaction were unveiled; next, we assessed the nature of the interactions driving photocatalytic CO2 activation and reduction on ZnSe quantum dots capped with organic ligands. Finally, the surface coverage of novel 2-D carbides (MXenes) under electrochemical conditions was thoroughly investigated, serving as groundwork for the rational design of cost-effective cathode materials for the electrosynthesis of valuable chemical feedstocks.
APPROVED
Keywords: chemistry; catalysis; computational; mxenes; electrocatalysis; photocatalysis; dft; sustainability; modelling; electrification